Ent-Kaurane Diterpenoids from Coffea Genus: An Update of Chemical Diversity and Biological Aspects - Víctor de C. Martins; Maria Alice E. da Silva; Valdir F. da Veiga; Henrique M. G. Pereira; Claudia M. de Rezende (Molecules)
Coffee is one of the most important beverages in the world and is produced from Coffea spp. beans. Diterpenes with ent-kaurane backbones have been described in this genus, and substances such as cafestol and kahweol have been widely investigated, along with their derivatives and biological properties. Other coffee ent-kaurane diterpenoids have been reported with new perspectives on their biological activities. The aim of this review is to update the chemical diversity of ent-kaurane diterpenoids in green and roasted coffee, detailing each new compound and reporting its biological potential. A systematic review was performed using the bibliographic databases (SciFinder, Web of Science, ScienceDirect) and specific keywords such as “coffea diterpenes”, “coffee diterpenes”, “coffee ent-kaurane diterpenes” and “coffee diterpenoids”. Only articles related to the isolation of coffee ent-kaurane compounds were considered. A total of 146 compounds were related to Coffea spp. since the first report in 1932. Different chemical skeletons were observed, and these compounds were grouped as furan-type, oxidation-type, rearrangement-type, lacton-type, and lactam-type, among others. In general, the new coffee diterpenoids showed potential as antidiabetic, antidiapogenic, α-glucosidade inhibition, antiplatelet activity, and Cav.3 inhibitors agents, revealing the possibilities for the design, discovery, and development of new drugs.